Inflammatory bowel disease and celiac disease: A bidirectional Mendelian randomization study - Shi, Yue; Feng, Sijia; Yan, Mengdie; Wei, Shuyan; Yang, Kejia; Feng, Yue (Frontiers in Genetics, 2022)
Objective: Although previous epidemiological studies have reported substantial links between inflammatory bowel disease (IBD), including Crohn’s disease (CD) and ulcerative colitis (UC), and celiac disease (CeD), the causal relationship between the two remains unknown. The purpose of the current study was to evaluate the bidirectional causation between IBD and CeD using Mendelian randomization (MR). Method: We obtained genome-wide association study (GWAS) summary data of IBD ( CD and UC) and CeD of thoroughly European ancestry from the IEU GWAS database. We screened eligible instrumental variables (IVs) according to the three assumptions of MR. MR was performed using MR-Egger, weighted median (WM), and inverse variance weighted (IVW) methods. The MR-Egger intercept and MR-PRESSO method investigated the horizontal pleiotropy effect. A leave-one-out analysis was performed to prevent bias caused by a single SNP. Results: The study assessed a bidirectional causal effect between CD and CeD; CD increased the risk of CeD (IVW odds ratio (OR) = 1.27, 95% confidence interval (CI) = 1.19–1.35, P = 3.75E-13) and vice-a-versa (IVW OR = 1.09, 95% CI = 1.05–1.13, P = 1.39E-05). Additionally, CeD was influenced by IBD (IVW OR = 1.24, 95% CI = 1.16,1.34, P = 9.42E-10) and UC (IVW OR = 0.90, 95% CI = 0.83–0.98, P = 0.017). However, we observed no evidence of a causal relationship between CeD and IBD (IVW OR = 1.00, 95% CI = 0.97–1.04, P = 0.900) or UC (IVW OR = 0.96, 95% CI = 0.92–1.02, P = 0.172). Conclusion: The present study revealed that IBD and CeD have a bidirectional causal relationship. However, it is slightly different from the results of previous observational studies, recommending that future studies focus on the mechanisms of interaction between CD and CeD.